A thorough study of Si nanowire FETs with 3D Multi-Subband Ensemble Monte Carlo simulations. (September 2019) - Donetti, L.; Sampedro, C.; Ruiz, F.G.; Godoy, A.; Gamiz, F.
Abstract: We thoroughly compare the DC electrical behavior of n-MOS transistors based on Si nanowires with 〈 1 0 0 〉 and 〈 1 1 0 〉 channel orientations by means of Multi-Subband Ensemble Monte Carlo simulations. We find that the drain current depends on the nanowire diameter and it is slightly, but consistently, larger for 〈 1 0 0 〉 than for 〈 1 1 0 〉 nanowires. The observed differences in mobility, velocity and spatial charge distribution are interpreted in terms of the effective masses and populations of the different Si conduction band valleys, whose sixfold degeneracy is lifted by quantum confinement in narrow nanowires. Finally, we study the scaling behavior for channel lengths down to 8 nm, concluding that the differences observed between orientations are minimal.